Содействие ЮНЕСКО в разработке и внедрении международных нормативов и стандартов библиотечной работы - Мацявичюте, Эляна (Knygotyra, 1987)
The internationally recognized standards, norms and methods of the library and information work are the main means of coordination and compatibility of library and information nets throughout the world. The international non-governmental organizations such as IFLA, FID, ICSU/AB, ISO TC-46 work much in the field of creation, ratifying and acknowledgement of such standards, norms and recommendations. Their work is coordinated by UNESCO which helps them by various means and creates the international standards and recommendations itself. The author speaks of the main forms of this work (conventions, international agreements, standards of ISO and others) and the main objects of the international standardization (library statistics, the exchange of publications, bibliographic description, the numerating systems of publications, cataloguing rules, international book tending system, terminology and so on).